Isolation and molecular identification of some pathological strains from the make-up of school students in Anbar province - Nada Ali Attallah Saleh (Peerian Journals Publishing, 2024)
This investigation conducted for isolation and molecular identification of some pathological strains from the make-up of school students in Anbar province. In 2022, researchers at the University of Baghdad, Iraq, gathered 120 samples of cosmetics used by female students. There was a total of 18–24-year-old women. Two separate samples of each face cream and lipstick were gathered using sterile cotton swabs and then sent to the lab to be cultured in enriched and selective medium. Then these were cultured on primary media, then were identified by using API kits. Molecular study was done for confirmation of different isolates in this study by using primers. a total of 65 samples (54.2%) were culturable, and 65 unique bacterial isolates were obtained from cosmetics. Additionally, 84.6% of the bacterial isolates were from the face cream, whereas just 15.4% were from the lipstick. Staphylococcus aureus (70% lipstick and 45.5% face cream) were the most often isolated germs. Staphylococcus aureus dominated Gram-positive bacterial isolates, whereas Escherichia coli dominated Gram-negative bacterial isolates. These bacteria were identified by using PCR which showed compatible results 100% with bacteriological way. In conclusion, Staphylococcus aureus was shown to be most bacteria that isolated from lip sticks and face cream
Keywords: Face Cream; Lip sticks; Anbar; Female